UJI AKTIVITAS ANTIHIPERLIPIDEMIA KOMBINASI EKSTRAK ETANOL DAUN BINAHONG (ANREDERA CORDIFOLIA (TEN.) STEENIS) DAN DAUN MURBEI (MORUS NIGRA L.) - Nur Aini, Nisrina
Hyperlipidemia is a metabolic disorder characterized by elevation(s) of total cholesterol, low density lipoprotein, and/or triglyceride exceeding the normal range. Empirically, either binahong leaves or mulberry leaves has an antihyperlipidemic activity. However, there is no scientific study on observing activity of both extracts in combination in improving lipid profile. This study aimed to determine antihyperlipidemic activity of both extracts in combination. A total of 28 rats were divided into seven groups: normal, control, simvastatin 3.6 mg/kg bw, binahong leaves extract 100 mg/kg bw (B100), mulberry leaves extract 200 mg/kg bw (M200), combination of binahong extract 50 mg/kg and mulberry 100 mg/kg (B50+M100), and combination of binahong extract 100 mg/kg bw and mulberry 200 mg/kg bw (B100+M200). Hyperlipidemia was induced by giving rats a high fat diet along with cholesterol (200 mg/kg), cholic acid (0.2% of chow), and propylthiouracil (10 mg/kg bw) for 30 days orally. Then, for the next 21 days, all groups except the normal and control were given the tested substances. Measurement of lipid profile was performed immediately after induction (T0) also after 7, 14, and 21 days after treatment (T7, T14, and T21, respectively). There were significant differences on a group of B100, M200, B50+M100, and B100+M200 compared to the control group at T14, with the value 37.32%, 42.87%, 54.10%, and 59.61% in reduction of total cholesterol and 43.16%, 48.08%, 60.72%, and 67.00% in reduction of LDL. In conclusion, group B100, M200, B50+M100, and B100+M200 reduced total cholesterol and LDL level remarkably at day 21. The combination of both extract (B100+M200) considerably shows better activity than either binahong extract (B100) or mulberry extract (M200).